The last empress - Min, Anchee, 1957- author 548750 (Boston : Houghton Mifflin, 2007)
At the end of the nineteenth century China is rocked by foreign attacks and local rebellions. The only constant is the power wielded by one woman, Tzu Hsi, also known as Empress Orchid, who must face the perilous condition of her empire and devastating personal losses. In this sequel to the bestselling "Empress Orchid", Anchee Min brings to life one of the most important figures in Chinese history, a very human leader who sacrifices all she has to protect both those she loves and her doomed empire.